Pollen morphology of rare species of Linum L. (Linaceae) from Poland - Kluza-Wieloch, Magdalena; Maciejewska-Rutkowska, Irmina; Wójtowicz, Wanda; Wiland-Szymańska, Justyna (Biodiversity: Research and Conservation, 2016)
The aim of the study was to describe pollen morphology and its variability of four Linum species: L. perenne subsp. extraaxillare, L. hirsutum, L. flavum and L. austriacum, all derived from Poland, but occurring in few natural sites within the country. Light and scanning electron microscopy was used and statistical analyses of quantitative pollen traits were performed. All taxa shared pollen grains which were 3-zonocolpate, isopolar, radiosymmetric, spheroidal and medium to large in size. Grains were semitectate, with the sculptural elements of the exine as gemmae or clavae. Additionally, upper parts of gemmae and clavae had a microstriate pattern. Despite great similarity among the investigated Linum species in pollen morphology, distinguishing features were determined.